Correlation of Seattle Angina Questionnaire score and post-procedural outcomes in patients undergoing multi-vessel coronary intervention. (14th October 2021) - Johal, G; Kyaw, H; Farhan, S; Gedela, M; Hooda, A; Goel, S; Iruvanti, S; Sartori, S; Mehran, R; Kini, A; Sharma, S
Abstract: Introduction: The Seattle Angina Questionnaire (SAQ) score has been used to assess angina severity in patients undergoing coronary intervention. However, assessment of clinical outcomes using the SAQ score in those with multi-vessel disease (MVD) requiring multiple interventions has not been determined. Purpose: To analyse patient-reported outcomes over time among individuals undergoing multiple staged interventions using serial SAQ scores. Methods: We performed a retrospective analysis of 531 consecutive elective patients who underwent multi-vessel coronary intervention from January 1, 2015, to December 31, 2018, at a single academic centre. We used a short-form version of the SAQ score calculator that is built into our hospital electronic medical record. Trained clinical staff administered the SAQ at the point of care before each procedure. We divided the baseline SAQ scores into three groups [Group 1: <50, Group 2: 50–66, Group 3: ≥67] and analysed the correlation between the scores and patient-reported angina symptoms before the final staged intervention. Post index procedural outcomes, including myocardial infarction, congestive heart failure, post-procedural bleeding, and blood transfusion were reported. Results: In all, 531 patients met inclusion and exclusion criteria. Patients' mean age was 65.66±10.30 years, and 78.3% of patients were males. Group 1 had an increased prevalence of diabetes (59.3% vs. 49.4% and 44%), prior coronary artery bypass surgery (CABG) (24.7% vs. 17.2% and 11.4%), a lower haemoglobin value (12.88±1.56 vs. 13.06±1.7 and 13.33±1.56) compared with group 2 and group 3. The rate of in-stent restenosis (ISR) was 18.7%, 11.5% and 8.6% in group 1, 2, and 3, respectively. Summary SAQ-7 values between interventions had improved significantly in group 1 (22.30±21.35) and group 2 (10.45±17.77), while group 3 failed to show any meaningful change (−1.09±14.79) (P<0.0001). [Table 1] The post-index-procedural outcomes were not statistically different among the three groups. In group 1, women (adjusted odds ratio [aOR]: 3.96; 95% confidence interval [CI]: 2.44 to 6.45; p<0.0001) and prior CABG patients (aOR: 2.03; 95% CI: 1.27 to 3.24; p=0.0031) had higher odds of SAQ-7 improvement between index and staged intervention. Conclusion: The lowest baseline SAQ group had a significant improvement of SAQ score between the index and a staged intervention. The study demonstrated that serial SAQ scores could be used as a surrogate to measure patient-reported outcomes in those with MVD undergoing multiple interventions. Funding Acknowledgement: Type of funding sources: None.